The Nonlinear Contact Simulation for Manufacturing Process by Using ANSYS Program as Case study with Cylindrical rolling contact - Ammar Dawood Ghali (Wasit Journal of Engineering Sciences)
Numerical simulation plays an indispensable role in the modern manufacturing process, especially in production operation and metal forming by using different of forming Dies Because it give perfect product design to improving quality and performance and reduce the time and cost .Because of the most of forming operation include contact option between the product surface (contact surface) and Die surface (Target surface) then the determination of the contact surface nature and material behavior ( uniform linear ) or ( not uniform nonlinear) that very effect on the carryout of forming process with required product .To improving simulation accuracy, approximations of linear behavior have become less  acceptable, while it is possible to perform nonlinear analysis and design more often  while minimizing approximations, the nonlinear analysis capabilities in general-purpose   programs such as ANSYS Mechanical.The significance of the research is into linear simulation analysis and its limitation and development to nonlinear simulation  where interest with the development manufacturing processes that including change in the geometry , properties and material behavior  through forming ,the search give an example of Case study with Cylindrical rolling contact that very important for wide application to manufacturing processes such as drawing ,Rolling ,Forging , Extrusion, Bending and other .The structural nonlinearities can be classified as geometric nonlinearity, material nonlinearity, and contact or boundary nonlinearity Numerical results indicate the success of ANSYS contact technologies in solving very large scale engineering problems especially large deformation frictional contact problems with the  new surface based contact elements have many advantages over the node based contact  elements .